1998
DOI: 10.1111/j.1939-1676.1998.tb02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Myotonia in 2 Domestic Cats

Abstract: ongenital myotonia was diagnosed in a male and a C female domestic cat. Physical examination revealed gait abnormalities and marked nonpainful enlargement of proximal appendicular muscles in both cats. A myotonic dimple was evoked in 1 cat. Thyrotropin-releasing hormone response testing was normal in 1 cat, and the adrenocorticotropic hormone response was normal in the other. Electromyography revealed classical myotonic discharges. Muscle biopsies from both cats were characterized by moderate hypertrophy by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2002
2002
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
3
18
0
Order By: Relevance
“…Variable findings have been described for both light and electron microscopy in feline MC, including occasional degeneration of individual myofibers associated with localized proliferation of sarcolemmal nuclei with few centrally located nuclei, moderate diffuse myofibril hypertrophy, rounding of the sarcoplasm, clear cytoplasmic vacuoles within many myofibers and mild dilatation of transverse T-tubules [27][29]. The mean myofiber perimeter and areas were previously measured and compared to age-matched controls using image software, showing increased perimeters and areas of myofibers in affected cats [27], [28]. The muscle profiles in this study showed hypertrophy of both type 1 and type 2 fibers with a normal mosaic pattern of muscle fiber types and no evidence of inflammation, necrosis, fibrosis or other specific cytoarchitectural abnormalities, consistent with a diagnosis of MC.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Variable findings have been described for both light and electron microscopy in feline MC, including occasional degeneration of individual myofibers associated with localized proliferation of sarcolemmal nuclei with few centrally located nuclei, moderate diffuse myofibril hypertrophy, rounding of the sarcoplasm, clear cytoplasmic vacuoles within many myofibers and mild dilatation of transverse T-tubules [27][29]. The mean myofiber perimeter and areas were previously measured and compared to age-matched controls using image software, showing increased perimeters and areas of myofibers in affected cats [27], [28]. The muscle profiles in this study showed hypertrophy of both type 1 and type 2 fibers with a normal mosaic pattern of muscle fiber types and no evidence of inflammation, necrosis, fibrosis or other specific cytoarchitectural abnormalities, consistent with a diagnosis of MC.…”
Section: Discussionmentioning
confidence: 96%
“…In goats, MC is inherited as an autosomal dominant trait [22]. Since the first description of caprine MC [23], historical, clinical, electrodiagnostic and histopathologic features have become well-established in horse [24], dog [25], [26] and cat models [27][30]. In the feline model, historical and clinical findings, along with routine blood testing, muscle percussion, cardiac examination, electrodiagnostic testing and muscle histopathology have been characterized in two related kittens and in four kittens from separate litters [21], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in CLCN1 have been identified in Australian cattle dogs, Miniature Schnauzers, Jack Russell terrier, and cats . Mutations in SCN4A have yet to be identified in dogs.…”
Section: Myotoniamentioning
confidence: 99%
“…Myotonia is the continued active contraction of a muscle after the cessation of voluntary effort and is characterised by muscle spasm and stiffness (Braund, 1986). Hereditary myotonia has been reported in a variety of species but only recently in the cat (Hickford et al, 1998;Toll et al, 1998). Myotonia can occur secondary to other disorders; muscular dystrophies and endocrinopathies or as a primary disorder; myotonia congenita.…”
Section: Congenital Myotoniamentioning
confidence: 99%